Oral Health Status and its Impact on Daily Performance in Adult Population with Diabetes (Update Dental College Journal, 2021)
Background: According to World Health Organization (WHO), diabetes mellitus, is a silent epidemic which affects large number of people around the world and is directly related to the oral health status of the patients.Objectives: To know the level of oral health and its impact on daily performance in adult population with Diabetes.Methods: A cross sectional study was comprised of group of 100 diabetic patients (males=68, females=32) from the OPD of Dhaka Dental College and Shaheed Suhrawardy Medical college, Dental unit of Dhaka. Oral health status is assessed by WHO described DMFT caries index and CPITN (community periodontal index treatment need). And oral impact on daily performance is determined by a modified form of OIDP index. Clinical examinations were included for the assessment of Dental Status. Chi-square was used for statistical evaluation.Results: Mean DMFT of the study population of Decayed, Missing and filled tooth were 3.89±3.35, 3.04±2.66 and 3.87±2.66 However, in case of CPITN index of the study population, Supragingival or subgingival pocket more than 6mm was in 32% cases. Mean scores of overall impacts on daily performances (OIDP) was 2.18±1.85. Bivariate analysis revealed that the self-reported oral impacts from the participants were not significantly associated (p≥0.05) with those who were diagnosed with presence of periodontal pockets more than 6 mm (32%).Conclusions: Oral health is an essential part of general health. Despite dental caries was comparatively low in diabetics, periodontal status was compromised which affected the participant’s daily life chiefly through difficulty in eating. Routinely follow-up of dental problems of the diabetics and oral health education is much required.Update Dent. Coll. j: 2021; 11 (1): 7-10